About the concept of improving border defense lines by means of landscape architecture - Shulyk, Vasyl; Shevchenko, Liudmyla; Cherniyavskyi, Volodymyr; Davydov, Anatoliy; Boborykin, Oleksiy (Landscape Architecture and Art, 2024)
The article presents the authors’ scientific work on the improvement of border defense lines with the help of landscape architecture. The highlighted issues are extremely relevant for the entire European community, especially for the residents of Ukraine. The territories of the states bordering the aggressor country must be strongly fortified, have defensive positions, points, fortifications and fences. Publications related to the war, the protection of the population, and the arrangement of life under martial law appeared in Ukraine. But the question of inclusion of landscape architecture means in defensive fortification lines rarely occurs in practice. The authors use an environmental approach to address these issues. The authors monitored the environment and considered the natural framework. It includes pronounced natural components - forests, open spaces, hydrographic network, etc. The methods and concepts of landscape architecture are also used in this study. A brief history of the development of the fortification case is presented. Fortifications that were built in European states in the period between the two world wars are considered. The most famous of them are: the Siegfried Line (Germany), the Maginot Line (France), the Mannerheim Line (Finland), the Metaxas Line (Greece), the “dragon teeth” tank barrier in the Alpine Mountains (“Alpine Wall”). An analysis of the current situation in the Russian-Ukrainian war was made. When strengthening borders, it is important to build dual-purpose artificial objects, use objects of natural or natural-anthropogenic origin, in particular – means of landscape architecture. It was found that, first of all, communication routes should have a clear system of defensive engineering structures. They must be activated immediately after the start of armed aggression against the country. The conditions of the geographical environment have always had a significant impact on the character, methods of conducting hostilities and their organization. This is also essential for arming soldiers, clarifying the possibilities of using the types and kinds of armed forces. Therefore, the influence of natural factors in military activity is significant. Analysis and assessment of the situation on the ground is an important step in the development of a preliminary plan of combat tasks. Those means of landscape architecture that are useful in the development of defense affairs have been identified. Among them are the relief of the area and vegetation, their characteristics, options for their solution. A system of fortified areas equipped with long-term fortifications and fences along the state border should be Ukraine’s nearest prospect. Areas of land of natural origin should become defensive fortifications during the period of active offensive actions of the enemy. In the southern and eastern regions of Ukraine, there are no natural barriers for enemy ground forces. Therefore, it is worth using agro-recreational and agro-production areas. It will be a significant addition to the main system of long-term fortification.